Proceedings of the 17th International Conference on Pattern Recognition, 2004. ICPR 2004. 2004
DOI: 10.1109/icpr.2004.1334073
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of clustering algorithms

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…Density-based clustering algorithms [4][5][6][7][8][9][10] circumvent this problem by using the number of data points in the neighborhood of a data point x i as a proxy for the data-point density. As a consequence, the objective function of these algorithms is often only given implicitly [11].…”
Section: Introductionmentioning
confidence: 99%
“…Density-based clustering algorithms [4][5][6][7][8][9][10] circumvent this problem by using the number of data points in the neighborhood of a data point x i as a proxy for the data-point density. As a consequence, the objective function of these algorithms is often only given implicitly [11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, when applying Algorithm 1, we set nbitr = 10. We take the k-means algorithm as the baseline since this technique is pretty closed in spirit to our proposal (transfer operations) and since it was shown that it provides relevant results compared to other clustering techniques [25]. In our experiments, we set k as the number of true classes for the k-means algorithm while keeping free this parameter for Algorithm 1.…”
Section: Experiments Settingsmentioning
confidence: 99%
“…Zhang et al [86] compared different distance measures using spectral clustering and found that the more complex DTW and LCSS distances did not perform significantly better than Euclidean variants because the shape of their paths were simple. The clustering comparison by Jain et al [87] suggest there may only be five major classes of clustering techniques to try as others produce similar partitions. A complete comparison of distance/similarity measures, clustering methods, and validation schemes is paramount to furthering trajectory based analysis rather than focusing on the learning methodology.…”
Section: Clustering Performancementioning
confidence: 99%